Perbandingan Latihan Otot Menggunakan Manual dan Robotik terhadap Kekuatan Otot Pasien Stroke Iskemik : Systematic Review - Handoyo, Soni; Awaludin, Sidik (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Stroke causes decreased motor function, requiring rehabilitation to restore muscle strength. Both manual and robotic interventions are used to improve muscle strength. Both robotic and manual methods offer efficiency and consistency of therapy. However, it is necessary to evaluate which method is superior in certain aspects. This study aims to disseminate the effectiveness of robotic muscle training compared to manual training in improving muscle strength, mobility, and quality of life in ischemic stroke patients. This systematic review uses articles published between 2016 and 2024 from the databases ScienceDirect, PubMed, Cochrance Library, Proquest, and Google Scholar. Articles were assessed using instruments from the Joana Briggs Institute. The use of a hand rehabilitation robot with force feedback demonstrated significant improvements in finger grip function in hemiplegic stroke patients, superior to manual therapies such as Tui Na massage using oils or herbal ointments. Muscle training using the robotic device proved more efficient and consistent, with significant improvements in FMA-Hand, ARAT, grip strength, and ROM (p 0.05). Tui Na massage was also effective in reducing spasticity and improving motor function, although less efficient than robotic therapy. The choice of therapy method should consider the patient's condition and rehabilitation goals. Both manual and robotic muscle training are effective in increasing extremity muscle strength in ischemic stroke patients. Robotic training is more time-efficient, while manual training is more flexible and adaptable to the needs of the patient. Keywords: Muscle Strength, Muscle Training, Manual, Robotic, Ischemic Stroke.  ABSTRAK Stroke menyebabkan penurunan fungsi motorik yang membutuhkan rehabilitasi untuk pemulihan kekuatan otot. Intervensi manual dan robotik digunakan untuk meningkatkan kekuatan otot. Penggunaan metode robotik dan manual menawarkan efisiensi dan konsistensi terapi. Namun, perlu dievaluasi metode mana yang lebih unggul dalam beberapa aspek tertentu. Penelitian ini bertujuan untuk mengevaluasi efektivitas penggunaan latihan otot dengan bantuan robotik dibandingkan dengan latihan manual dalam meningkatkan kekuatan otot, mobilitas, dan kualitas hidup pasien stroke iskemik. Systematic Review ini menggunakan artikel yang dipublikasi dari tahun 2016-2024 bersumber dari database Science Direct, Pubmed, Cochrance Library, Proquest dan Google Scholar. Penilaian artikel dilakukan dengan instrumen dari Joana Briggs Institute.  Penggunaan robot rehabilitasi tangan dengan  umpan balik gaya menunjukkan peningkatan signifikan pada fungsi genggaman jari pasien stroke hemiplegia, lebih baik dibandingkan terapi manual seperti pijat Tui Na yang menggunakan minyak atatu salep herbal. Latihan otot menggunakan alat bantu robot terbukti lebih efisien dan konsisten, dengan peningkatan signifikan pada FMA-Hand, ARAT, grip strength, dan ROM (p 0,05). Pijat Tui Na juga efektif mengurangi spastisitas dan meningkatkan fungsi motorik, meskipun kurang efisien dibandingkan robotik. Pemilihan metode terapi harus mempertimbangkan kondisi pasien dan tujuan rehabilitasi.Latihan otot manual dan robotik keduanya efektif meningkatkan kekuatan otot ekstremitas pada pasien stroke iskemik. Latihan robotik lebih efisien dalam waktu, sementara manual lebih fleksibel sesuai kebutuhan Kata Kunci: Kekuatan Otot, Latihan Otot, Manual, Robotik, Stroke Iskemik.